Analysis of The Implementation of Good Village Governance Principles in Optimizing Village Fund Allocation Management in Tanjungtani Village - Satya Putri Mardiana; Sri Kalimah; Beby Hilda Agustin (Dinasti Publisher, 2025)
A substantial Village Fund Allocation (ADD) can certainly support a village's progress in village development and governance. The village financial management crisis remains an unresolved issue in Indonesia. Frequently encountered issues in village financial management include effectiveness, efficiency, prioritization, leakage and irregularities, and low professionalism. This study employed a qualitative descriptive method. Data sources included primary and secondary sources, with interviews and documentation as data collection techniques. The results indicate that the implementation of Good Village Governance principles in Tanjungtani Village has been quite successful, particularly in aspects of participation in planning and implementation information, transparency through public media, and accountability through open reporting. However, community involvement in evaluation remains limited. This study recommends increasing community participation in the evaluation stage and improving the information system to improve the quality of village fund governance.